2016
DOI: 10.1097/id.0000000000000460
|View full text |Cite
|
Sign up to set email alerts
|

Flap Designs for Implant-Related Surgical Procedures

Abstract: This review revealed that the FL technique might be more appropriate in immediate implant loading cases. This specific technique results in shallower biological width, reduced inflammation, less morbidity with guided implant placement, and better esthetics in comparison with the FT technique. The implant survival rates are not significantly different between the 2 flap techniques. With respect to crestal bone resorption in FL and FT, it is inconclusive, depending on the study type (human or animal).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…This phenomenon may due to destruction of the blood supply by the creation of a mucoperiosteal flap. Flap elevations may cause a greater number of inflammatory cells, a higher probability of infection, and a longer healing time 49 . Conversely, the meta‐regression analysis in the present review did not establish a significant difference between the flap elevation group and the flapless group regarding their correlation with CHBD or CVBD.…”
Section: Discussioncontrasting
confidence: 81%
“…This phenomenon may due to destruction of the blood supply by the creation of a mucoperiosteal flap. Flap elevations may cause a greater number of inflammatory cells, a higher probability of infection, and a longer healing time 49 . Conversely, the meta‐regression analysis in the present review did not establish a significant difference between the flap elevation group and the flapless group regarding their correlation with CHBD or CVBD.…”
Section: Discussioncontrasting
confidence: 81%
“…It was found that cell inflammatory factors played an important role in ischemia-reperfusion injury, which can lead to tissue morphological damage and dysfunction (10,11). Therefore, anti-inflammatory response is a major research focus aiming to alleviate ischemia-reperfusion injury and improve flap survival rate (12).…”
Section: Discussionmentioning
confidence: 99%
“…Although some details can be modified during the performance of the procedure, detailed planning allows for a better clinical outcome. (Al-Juboori, 2016) The main aim of this research was to describe all aspects of surgical manipulation of the soft and hard tissues during the dental implantology procedures. We have made adequate literature research on Pub Med, as most commonly used internet database, for articles relevant to our topic-surgical manipulation of the soft and hard tissues during the dental implantology procedures published in the last two decades , and the type of articles were Clinical Trial, Journal Article, Randomized Controlled Trial, Review, Comparative study and English was chosen as the language and humans as the species.…”
Section: Introductionmentioning
confidence: 99%